2018
DOI: 10.1016/j.apergo.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Tablet form factors and swipe gesture designs affect thumb biomechanics and performance during two-handed use

Abstract: Tablet computers' hardware and software designs may affect upper extremity muscle activity and postures. This study investigated the hypothesis that forearm muscle activity as well as wrist and thumb postures differ during simple gestures across different tablet form factors and touchscreen locations. Sixteen adult (8 female, 8 male) participants completed 320 tablet gestures across four swipe locations, with various tablet sizes (8″ and 10"), tablet orientations (portrait and landscape), swipe orientations (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The aim of this study was to build upon a previous thumb swiping study to determine the effect of sex/gender for participants' thumb swiping performance, forearm muscle activity, and self-reported discomfort during thumb swiping tasks (Coppola et al, 2018). Overall, there was a significant effect of sex/gender in addition to the other independent variables (tablet size, tablet orientation, gesture location, gesture direction, and gesture orientation) on many forearm muscles.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The aim of this study was to build upon a previous thumb swiping study to determine the effect of sex/gender for participants' thumb swiping performance, forearm muscle activity, and self-reported discomfort during thumb swiping tasks (Coppola et al, 2018). Overall, there was a significant effect of sex/gender in addition to the other independent variables (tablet size, tablet orientation, gesture location, gesture direction, and gesture orientation) on many forearm muscles.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, no studies have investigated the sex/gender differences in thumb swiping tasks on touchscreen devices. Therefore, the purpose of this study was to use the data previously reported in Coppola et al (2018) to explore the effect of sex/gender during thumb swiping tasks with different tablet hardware and software characteristics on forearm muscle activity, performance, and usability. Specifically, we hypothesize that female participants will use more muscle activity across tasks, perform worse on farther reach swipe targets, and report higher discomfort and difficulty for larger tablets.…”
Section: Introductionmentioning
confidence: 99%
“…While the initial direction, radial or ulnar deviation, for backward page turning or swiping was different depending on the hand, left or right, in use, only medial radial deviation was significantly higher for page turning. The process of semi-grasping, elevating, and releasing a book page requires more complex wrist motion than swiping on a tablet, and swiping requires sustained contact in a more constrained space [ 4 ]. Greater medial extension angle and ROM for typing versus texting and maximum medial extension angle and lateral extension ROM during female manual versus cell phone calculator use could also be associated with device attributes, specifically key activation [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bimanual perceived grip comfort should be considered. The M ( SD ) side bezel width of 151 tablet PCs, 15.2 (2.5) mm, can be used as a reference considering that tablet PC touch interaction studies (Coppola, Lin, Schilkowsky, Arezes, & Dennerlein, 2018; Odell & Chandrasekaran, 2012; Oulasvirta et al, 2013; Trudeau, Catalano, Jindrich, & Dennerlein, 2013) commonly assumed the same gripping method (hands holding respective sides of the device with thumbs on respective side bezels), similar to the gripping methods used for Grip FF .…”
Section: Discussionmentioning
confidence: 99%